Authenticity: Do City Image Affect Revisit Intentions to Banda Aceh, Indonesia? - Mardiah, Rima Humaira; Riyaldi, Muhammad Haris; Halim, Hendra; Najla, Najla; Nurlina, Eka (Universitas Syiah Kuala, 2025)
This study aims to analyze the effect of city authenticity on revisit intention for religious tourism in Banda Aceh, with city image acting as a mediating variable. The research was conducted at major religious tourist destinations, such as the Baiturrahman Grand Mosque and other historical sites that serve as symbols of the citys identityThis study utilized a quantitative approach with a survey method, collecting data through closed-ended questionnaires that were directly distributed to 108 respondents chosen through purposive sampling. The data were then analyzed using path analysis to investigate the direct and indirect relationships between the variablesThe findings indicate that city authenticity positively and significantly affects both city image and tourists intention to revisit. Additionally, city image has been shown to exert a positive influence on revisit intention and acts as a mediator in the relationship between city authenticity and revisit intention within the context of religious tourism in Banda Aceh. These findings highlight the importance of preserving the citys authenticity and strengthening its positive image to increase tourist loyalty to revisit religious tourism destinations. The practical implication is that the local government should maintain the authenticity of city elements and enhance the city image to ensure the sustainability of religious tourism in the future.